The Physical Progress of a Professional Scottish Soccer Academy Over a Ten-Year Period - Craig TP; Maughan P; McArdle MP; Clark DR; Reid D (Dove Medical Press, 2024)
Thomas P Craig,1 Patrick Maughan,1 Michael Peter McArdle,2 David R Clark,1 Donald Reid3 1School of Health Sciences, Robert Gordon University, Aberdeen, UK; 2The Scottish Football Association, Glasgow, UK; 3School of Biodiversity, One Health and Veterinary Medicine, University of Glasgow, Glasgow, UKCorrespondence: Thomas P Craig, Email T.P.Craig@outlook.comBackground: Increases in high-intensity locomotor activity of match play have been recorded in elite soccer. This places an onus on academy practitioners to develop players for the future demands of the game. At an academy level, locomotor data are not available for analysis over a longitudinal period, and thus changes can only be assessed with physical attribute assessment. The aim of the present study is to establish if changes in physical capacity were observed in a professional Scottish soccer academy over a ten-year period.Methods: A retrospective analysis was completed where linear mixed effect (LME) models were individually fitted to explain variation across each measure of physical capacity. Model selection was undertaken with likelihood ratio tests where the initial complex models were compared to simpler nested models to arrive at the final model by maximum likelihood.Results: The main findings were that most recent players' sprint test data revealed a significant improvement in 5m, 10m and 20m sprint performance, greater increases in CMJ performance in older age groups, and greater increases in YYIR1 performance at U13 and U14. Most physical results showed increased performance with greater relative height and weight.Conclusion: Players recruited more recently to academies are fitter than they were previously. Reference values within clubs that establish first team requirements will contribute to appropriate planning and implementation of training.Keywords: player development, first team transition, talent development, soccer, football, physical profiles